Implementation of Universal Design to Achieve Equality for Persons with Disabilities in Indonesia - Baiq Salma Widiana Sari (Yayasan Tranformasi Aksara Digital, 2024)
Equality for persons with disabilities is part of human rights that must be guaranteed by the state. The Convention on the Rights of Persons with Disabilities, which has been ratified by Indonesia through Law Number 19 of 2011, emphasizes the importance of applying Universal Design principles in creating an inclusive environment for persons with disabilities. This research aims to analyze the extent to which Universal Design principles have been implemented in policies and regulations in Indonesia. Using a normative juridical method through legislative and conceptual approaches, this research examines various regulations related to accessibility and the rights of persons with disabilities and compares them with international standards. The findings show that regulations in Indonesia still place Universal Design as a mere technical aspect, not as part of the fundamental rights that the state must guarantee. As a result, accessibility for persons with disabilities in public spaces, including places of worship, is still not optimal. This study confirms the need for a more comprehensive policy reformulation so that Universal Design is recognized as a human right in the Indonesian legal system. In conclusion, without significant changes in regulations and policies, the implementation of Universal Design in Indonesia will remain partial and not fully support the realization of equality for persons with disabilities.